Diagnostic performance of microRNAs in the detection of heart failure with reduced or preserved ejection fraction: a systematic review and meta‐analysis. (27th October 2022) - Parvan, Reza; Hosseinpour, Milad; Moradi, Yousef; Devaux, Yvan; Cataliotti, Alessandro; da Silva, Gustavo J.J.
Abstract : Aim: Chronic heart failure (CHF) can be classified as heart failure with preserved ejection fraction (HFpEF) or with reduced ejection fraction (HFrEF). Currently, there is an unmet need for a minimally invasive diagnostic tool for different forms of CHF. We aimed to investigate the diagnostic potential of circulating microRNAs (miRNAs) for the detection of different CHF forms via a systematic review and meta‐analysis approach. Methods and results: Comprehensive search on Medline, Web of Science, Scopus, and EMBASE identified 45 relevant studies which were used for qualitative assessment. Out of these, 29 studies were used for qualitative and quantitative assessment and allowed to identify a miRNA panel able to detect HFrEF and HFpEF with areas under the curve (AUC) of 0.86 and 0.79, respectively. A panel of eight miRNAs (hsa‐miR‐18b‐3p, hsa‐miR‐21‐5p, hsa‐miR‐22‐3p, hsa‐miR‐92b‐3p, hsa‐miR‐129‐5p, hsa‐miR‐320a‐5p, hsa‐miR‐423‐5p, and hsa‐miR‐675‐5p) detected HFrEF cases with a sensitivity of 0.85, specificity of 0.88 and AUC of 0.91. A panel of seven miRNAs (hsa‐miR‐19b‐3p, hsa‐miR‐30c‐5p, hsa‐miR‐206, hsa‐miR‐221‐3p, hsa‐miR‐328‐5p, hsa‐miR‐375‐3p, and hsa‐miR‐424‐5p) identified HFpEF cases with a sensitivity of 0.82 and a specificity of 0.61. Conclusions: Although conventional biomarkers (N‐terminal pro‐B‐type natriuretic peptide and B‐type natriuretic peptide) presented a better performance in detecting CHF patients, the results presented here pointed towards specific miRNA panels with potential additive values to circulating natriuretic peptides in the diagnosis of different classes of CHF. Equally important, miRNAs alone showed a reasonable capacity for 'ruling out' patients with HFrEF or HFpEF. Additional studies with large populations are required to confirm the diagnostic potential of miRNAs for sub‐classes of CHF. Abstract : MicroRNA‐driven diagnostic biomarkers for heart failure with reduced or preserved ejection fraction. AUC, area under the receiver operating characteristic curve; BNP, B‐type natriuretic peptide; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; NT‐proBNP, N‐terminal prohormone B‐type natriuretic peptide; Sens, sensitivity; Spec, specificity.